2020
DOI: 10.3390/e22020193
|View full text |Cite
|
Sign up to set email alerts
|

Deep Residual Learning for Nonlinear Regression

Abstract: Deep learning plays a key role in the recent developments of machine learning. This paper develops a deep residual neural network (ResNet) for the regression of nonlinear functions. Convolutional layers and pooling layers are replaced by fully connected layers in the residual block. To evaluate the new regression model, we train and test neural networks with different depths and widths on simulated data, and we find the optimal parameters. We perform multiple numerical tests of the optimal regression model on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…ResNet introduced shortcut connection to train very deep convolutional models, with no extra parameters and no added computation complexity. For this nonlinear regression implementation, we replace the convolution layers by fully connected layers, as shown to work in [14].…”
Section: Model 2: Resnetregmentioning
confidence: 99%
“…ResNet introduced shortcut connection to train very deep convolutional models, with no extra parameters and no added computation complexity. For this nonlinear regression implementation, we replace the convolution layers by fully connected layers, as shown to work in [14].…”
Section: Model 2: Resnetregmentioning
confidence: 99%
“…We use a regression ResNet model (Chen et al, 2020) to predict the repulsive pose. The results in the study by Shi et al (2020) have shown that the MAEs of the model on the test set are less than 8.…”
Section: Repulsive Pose Predictionmentioning
confidence: 99%
“…We use a ResNet-based network for the regression task (Chen et al, 2020). The architecture of the network is shown in Figure 3.…”
Section: Resnet For Regressionmentioning
confidence: 99%
See 2 more Smart Citations